Energy conversion from biodegradation of non-thermal pre-treated algae biomass for microbial fuel cell / Muhammad Haikal Zainal … [et al.] - Zainal, Muhammad Haikal; Hassan, Oskar Hasdinor; Ab Samad, Liana Shakira; Ali, Ab Malik Marwan; Yahya, Muhd Zu Azhan (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2016)
Strength and complexity of algae cell wall structures provides difficulty for microbial substrate digestion. Therefore, pre-treatment is required to break the algae cell wall. There are several types of algae cell wall pre-treatment before degradation process. Among of these methods, freeze drying method is able to breakdown algae cell walls and preserve algae cell constituents simultaneously. Freeze dried (non-thermal pre-treatment) Chlorella vulgaris microalgae biomass was used as microbial substrate consumption in double chamber Microbial Fuel Cell (MFC) to generate bio electricity. As a result, the treatment efficiency obtained in terms of Chemical Oxygen Demand (COD) removal efficiency is 63.5%. Based on the power curve obtained, the maximum power density is 8.94 m W/m² using 2.5 g/L of substrate concentration. At substrate concentration of 5.0 g/L, the MFC has COD removal efficiency of 52.38% and maximum power density of 2.87mW/m². At the substrate concentration of 1.0 g/L, the MFC has COD removal efficiency is 86.8%, and maximum power density of 0.11 m W/m². MFC with different freeze dried algae substrate of 1.0 g/L, 2.5 g/L and 5.0 g/L has Coulombic efficiency (CE) of 1.56 %, 18.6% and 13.1%, respectively. These results reveal that the use of freeze dried microalgae biomass could be a promising candidate in the application of MFC.